A clinical study of association of genital tuberculosis with infertility in a tertiary centre of Jharkhand, India - Kamal, Samarina; Singh, Vandita; Singh, Shashibala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The worldwide incidence of GTB is approximately 5- 10% in infertile women. It varies from as low as 0.69% in some developed countries to as high as 19% in India. It is diagnosed by culture of the tubercle bacillus from tissue sampled from the genital tract is the yardstick for diagnosis and remains the gold standard. Methods: A prospective study was carried out between January 2012 and January 2015 on 100 women presenting with infertility. Results: A total (27%) women were diagnosed as genital tuberculosis by combination of hystero laparoscopic findings, histopathological and endometrial DNA-PCR technique confirmation. Of these (40.62%) had secondary infertility and remaining (59.38%) had primary infertility. (15.62%) were previously diagnosed with pulmonary or extra pulmonary tuberculosis and had completed a full course of Anti-tubercular treatment as per WHO CAT 1 regime. Conclusions: Therefore, in countries where TB is endemic, early and aggressive strategies should be pursued to diagnose and treat TB.